(1+j)(6-2j)=

Simple and best practice solution for (1+j)(6-2j)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1+j)(6-2j)= equation:


Simplifying
(1 + j)(6 + -2j) = 0

Multiply (1 + j) * (6 + -2j)
(1(6 + -2j) + j(6 + -2j)) = 0
((6 * 1 + -2j * 1) + j(6 + -2j)) = 0
((6 + -2j) + j(6 + -2j)) = 0
(6 + -2j + (6 * j + -2j * j)) = 0
(6 + -2j + (6j + -2j2)) = 0

Combine like terms: -2j + 6j = 4j
(6 + 4j + -2j2) = 0

Solving
6 + 4j + -2j2 = 0

Solving for variable 'j'.

Factor out the Greatest Common Factor (GCF), '2'.
2(3 + 2j + -1j2) = 0

Factor a trinomial.
2((3 + -1j)(1 + j)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(3 + -1j)' equal to zero and attempt to solve: Simplifying 3 + -1j = 0 Solving 3 + -1j = 0 Move all terms containing j to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1j = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1j = 0 + -3 -1j = 0 + -3 Combine like terms: 0 + -3 = -3 -1j = -3 Divide each side by '-1'. j = 3 Simplifying j = 3

Subproblem 2

Set the factor '(1 + j)' equal to zero and attempt to solve: Simplifying 1 + j = 0 Solving 1 + j = 0 Move all terms containing j to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + j = 0 + -1 Combine like terms: 1 + -1 = 0 0 + j = 0 + -1 j = 0 + -1 Combine like terms: 0 + -1 = -1 j = -1 Simplifying j = -1

Solution

j = {3, -1}

See similar equations:

| 6x+7(9-x)=61 | | 5x=6x-28 | | (4+3j)-(5j-6)= | | X^2+100=9x^2 | | 3(p^2-16p+81)=81 | | 12x^2-5x-3= | | 5x^2-8x-4= | | x+4=2x-1 | | 3k-3=2k+6 | | 5x+2=77 | | 54y-2y^3= | | 4x^2+28x-150=0 | | 12x^2-20x+3=0 | | 2x^2+30x+52= | | 4(2+j)-3(6+2j)+7j= | | 2(4x-7)=5(-2x-9)-5 | | 2g^2-14g+20=0 | | 4(x-2)=x-20 | | 3x-7=3x+5 | | 2(3x-1)=x+13 | | (x^2-4x+6)(2x^2+8x-1)=0 | | (x^2-4x+6)(2x^2+8x-1)=1 | | 9x+10=7x+2 | | -6y=d | | -6y=da | | w-6c=9 | | 10x+y-xy=58 | | r+5=2r-1 | | (x+5)(x-1)=0 | | .2(4y+5)=3+0.25(y+3) | | 2z^2+6z+17=0 | | 200=50e^3x |

Equations solver categories